The Effect of Social Presence and Quality of User Generated Content (UGC) on Consumer Trust through Electronic Word of Mouth (EWOM) in FEB UNJ Students on the TikTok Platform - Teja Supraba; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of Social Presence and User-Generated Content (UGC) Quality on Consumer Trust through Electronic Word of Mouth (eWOM) among TikTok users in the Faculty of Economics and Business, University of Jakarta. This phenomenon is important because social interaction and content quality on video-based platforms are believed to shape digital trust through the process of communication between users. The study uses a quantitative approach with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method on 185 respondents. The results show that Social Presence and UGC Quality have a significant positive effect on eWOM and Trust, and eWOM mediates this relationship. These findings confirm that digital trust is not only built from the quality of information, but also from social closeness and user participation in eWOM. This study reinforces Social Presence Theory and Information Quality Theory, and provides practical contributions for marketers and content creators in building trust through authentic interactions and credible content on TikTok